2020
DOI: 10.25077/aoj.4.1.125-136.2020
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Histopathology Type and Neoadjuvant Chemotherapy Response in IB2 and IIA2 Cervical Cancer

Abstract: AbstrctBackground: Cervical cancer was the fourth common cancer in women in the world and the second most in Indonesia. Chemotherapy has been evaluated as a therapy strategies to treat stage IB2 and IIA2 cervical cancer. Neoadjuvant chemotherapy was still being a controversy for the chemotherapy resistance patient. This would delay the provision of definitive therapy. A marker is needed to identify patient which more relatively resistant to chemotherapy. Squamous Cell Carcinoma (SCC) type was known be have bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The after-effects of this study by Khatimah, (9) showed 35 subjects, of which 25 subjects (71,4 %) were squamous cell carcinoma type, followed by 10 subjects (28,6 %) in the adenocarcinoma group. The most common type of squamous cell carcinoma is found in around 80 % and 20 % of adenocarcinoma types, while other histological types are very rare in cervical cancer.…”
Section: Characteristics Of Research Subjectsmentioning
confidence: 55%
“…The after-effects of this study by Khatimah, (9) showed 35 subjects, of which 25 subjects (71,4 %) were squamous cell carcinoma type, followed by 10 subjects (28,6 %) in the adenocarcinoma group. The most common type of squamous cell carcinoma is found in around 80 % and 20 % of adenocarcinoma types, while other histological types are very rare in cervical cancer.…”
Section: Characteristics Of Research Subjectsmentioning
confidence: 55%